Predictors of juvenile court dispositions in a first-time offender population - Kalmbach, Karen C. (Applied psychology in criminal justice, 2012)
Scholars and policy makers have long been troubled by the potential for some youth to receivedisparate sanctioning as a function of extralegal factors, especially against the backdropof ethnic/racial minority group overrepresentation in the juvenile justice system asa whole. Beginning in the late 1990s, many states began to adopt a graduated sanctionsmodel in response to the emerging 'get tough' zeitgeist of the day. Originally intended bythe federal government to reinforce juvenile accountability and to ensure equitable treatmentof all youth in custody, some stakeholders began to note concerns about unevenoutcomes in the use of graduated sanctioning schemes. Specifically, data across multiplejurisdictions suggested that racial and ethnic minority youth were receiving more restrictivethan expected sanctions. The current study in one large urban jurisdiction explored thisissue in a group of 2,786 racially and ethnically diverse first-time juvenile male offenders(ages 10-17). Results indicated that race/ethnicity was not a predictor of receiving a morerestrictive than expected sanction; however, variables related to offending (offense severity,history of violence), age (older), and parental supervision (inadequate) were significantpredictors of such departures.